¿Debemos pensar en un estimator diferente para la mediana? (2014)
The median, one of the most popular measures of central tendency widely-used in the statistical practice, is often described as the numerical value separating the higher half of the sample from the lower half. Despite its popularity and applications, many people are not aware of the existence of several formulas to estimate this parameter. We present the results of a simulation study comparing the classic and the Harrell-Davis (Harrell & Davis 1982) estimators of the median for eight continuous statistical distributions. It is shown that, relatively to the latter, the classic estimator performs poorly when the sample size is small. Based on these results, we strongly believe that the use of a better estimator of the median must be promoted.